2017
DOI: 10.1002/jssc.201700641
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative study on chemical components and anti‐inflammatory effects of Panax notoginseng flower extracted by water and methanol

Abstract: Methanol and water are commonly used solvents for chemical analysis and traditional decoction, respectively. In the present study, a high-performance liquid chromatography with ultraviolet detection method was developed to quantify 11 saponins in Panax notoginseng flower extracted by aqueous solution and methanol, and chemical components and anti-inflammatory effects of these two extracts were compared. The separation of 11 saponins, including notoginsenoside Fc and ginsenoside Rc, was well achieved on a Zorba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Most of the products have high bioavailability and bioactivity. Moreover, previous studies suggest that intestinal microflora produce different types of glycosidases, which dominate the hydrolysis of ginsenosides . In the present study, the biotransformation of Fc was studied in the gut microflora and seven deglycosylation products were detected.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Most of the products have high bioavailability and bioactivity. Moreover, previous studies suggest that intestinal microflora produce different types of glycosidases, which dominate the hydrolysis of ginsenosides . In the present study, the biotransformation of Fc was studied in the gut microflora and seven deglycosylation products were detected.…”
Section: Discussionmentioning
confidence: 84%
“…To further verify the influence of intestinal microbiota on Fc metabolism, the metabolites of Fc were qualitatively and quantitatively analyzed in a systematic manner. In normal rats, Fc was metabolized to ten deglycosylate metabolites via stepwise deglycosylation . After administration of the antibiotic cocktail in rats for 6 days, the activities of xylosidase and glucosaccharase in the antibiotic‐treated rats was decreased by 80 and 60% for the normal rats, respectively, and deglycosylation of Fc was drastically abrogated.…”
Section: Discussionmentioning
confidence: 99%
“…The ginsenosides were separated with a flow rate of 0.75 mL/min, column temperature of 23 °C, and mobile phase gradient with the following conditions: isocratic elution for 18 % ACN for 18 min, increased to 33 % ACN over 38 min, and held for 9 min. Similar approaches have been reported that require lengthy separation times [17,18].…”
Section: Resultsmentioning
confidence: 55%
“…Dammarane-type triterpene saponins, including ginsenosides and notoginsenosides, contributed to the abovementioned pharmacological effects, and these saponins can be divided into PPD and protopanaxatriol (PPT) types based on their aglycone skeleton [9]. It has been demonstrated that Fc exhibits various pharmacological activities as a folk medicine or dietary supplement [10, 11]. However, little information regarding the effects of Fc on reendothelialization and the underlying mechanism is available.…”
Section: Introductionmentioning
confidence: 99%